Monocytes and the Host Response to Fungal Pathogens - Heung, Lena J. (Frontiers in Cellular and Infection Microbiology, 2020)
Monocytes and their derivatives, including macrophages and dendritic cells, play diverse roles in the response to fungal pathogens. Sensing of fungi by monocytes triggers signaling pathways that mediate direct effects like phagocytosis and cytokine production. Monocytes can also present fungal antigens to elicit adaptive immune responses. These monocyte-mediated pathways may be either beneficial or harmful to the host. In some instances, fungi have developed mechanisms to evade the consequences of monocyte activation and subvert these cells to promote disease. Thus, monocytes are critically involved in mediating the outcomes of these often highly fatal infections. This review will highlight the roles of monocytes in the immune response to some of the major fungi that cause human disease, including Aspergillus, Cryptococcus, Candida, Histoplasma, Blastomyces, and Coccidioides, and discuss potential strategies to manipulate monocyte responses in order to enhance anti-fungal immunity in susceptible hosts.